The Cinderella story of sucrose hydrolysis: Alkaline/neutral invertases, from cyanobacteria to unforeseen roles in plant cytosol and organelles - Vargas, Walter Alberto (2010)
Over the past decades, considerable advances have been made in understanding the crucial role of sucrose and the regulation of its metabolism in plant life. Recent studies in cyanobacteria and the analysis of several genomic sequences point towards an ancient origin of plant sucrose metabolism before the cyanobacterial phylogenetic radiation. In agreement with the generally accepted cyanobacterial endosymbiotic origin of plant chloroplasts, most of the cyanobacterial genes were transferred to the nucleus and their protein products were preferentially re-imported to the plant organelle. In the case of sucrose metabolism, the enzymes sucrose-phosphate synthase (SPS) and sucrose-phosphate phosphatase (SPP), responsible of the disaccharide synthesis, and sucrose synthase (SuS) and alkaline/neutral invertases (A/N-Inv), involved in sucrose cleavage, appear to have a cyanobacterial origin. However, whereas SPS and SPP are likely to be exclusively localized in the cytosol of modern plant cells, SuS and A/N-Inv isoforms are distributed between the cytosol and different subcellular locations. Particularly, A/N-Invs are the least studied proteins of sucrose catabolism. They were somewhat underestimated, and thought to play no relevant role in carbon metabolism. However, some striking recent findings about the presence of A/N-Inv forms inside plant organelles, as well as the description of novel physiological functions, led us to re-evaluate the importance of these Cinderella enzymes. The additional roles uncovered for A/N-Invs disclose new scenarios for the interconnection between the cytosol and organelles and for complex crosstalk signalling pathways.